2023
DOI: 10.1111/ene.16054
|View full text |Cite
|
Sign up to set email alerts
|

SerpinA1 levels in amyotrophic lateral sclerosis patients: An exploratory study

Ilaria Martinelli,
Elisabetta Zucchi,
Cecilia Simonini
et al.

Abstract: BackgroundSerpinA1, a serine protease inhibitor, is involved in the modulation of microglial‐mediated inflammation in neurodegenerative diseases. We explored SerpinA1 levels in cerebrospinal fluid (CSF) and serum of amyotrophic lateral sclerosis (ALS) patients to understand its potential role in the pathogenesis of the disease.MethodsSerpinA1, neurofilament light (NfL) and heavy (NfH) chain, and chitinase‐3‐like protein‐1 (CHI3L1) were determined in CSF and serum of ALS patients (n = 110) and healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that SERPINA1 [563], LRRK2 [522], CHRNA4 [564], CD22 [565], TF (transferrin) ssociated tyrosine kinase) [579], FGF14 [580], INSC (INSC spindle orientation adaptor protein) [581], BARHL1 [582], PRKCH (protein kinase C eta) [583], SLC24A4 [584], TMEM176B [585], MBP (myelin basic protein) [586], ACAN (aggrecan) [587], SHH (sonic hedgehog signaling molecule) [588], SIRT2 [589], RBP4 [590], ISM1 [591], HOXB6 [592], CDH13 [593], NTF3 [594], TRPC6 [595], MMP3 [596], HLA-DRB5 [597], HLA-DRB1 [546], CD74 [598], VWF (von Willebrand factor) [599], MDGA1 [600], ANGPT2 [601], NEDD4L [602], CASP1 [603], CHRNA5 [604], CCND2 [605], BRCA2 [606], TET1 [607], ZBTB20 [608], OAS1 [609], EGFR (epidermal growth factor receptor) [610], ABCA1 [611], PLXNA4 [612], FOXG1 [613], WEE1 [433], MAP1B [614], ANK1 [615], GRM3 [436], COMT (catechol-O-methyltransferase) [616], SLC10A4 [617], GPR39 [618] and LIFR (LIF receptor subunit alpha) [562] could promote Alzheimer’s disease progression. SERPINA1 [619], LRRK2 [620], CHRNA4 [621], TLR2 [622], MOBP (myelin associated oligodendrocyte basic protein) [623], AATK (apoptosis associated tyrosine kinase) [624], MBP (myelin basic protein) [625], SHH (sonic hedgehog signaling molecule) [626], XDH (xanthine dehydrogenase) [627], RBP4 [628], GRIA2 [629], NR3C2 [630], HLA-DRB5 [631], HLA-DRA [631], NEDD4L [632], CASP1 [633], EFNB2 [634], CYP7B1 [635], EGFR (epidermal growth factor receptor) [636], MAP1B [637], GRM3 [638<...…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SERPINA1 [563], LRRK2 [522], CHRNA4 [564], CD22 [565], TF (transferrin) ssociated tyrosine kinase) [579], FGF14 [580], INSC (INSC spindle orientation adaptor protein) [581], BARHL1 [582], PRKCH (protein kinase C eta) [583], SLC24A4 [584], TMEM176B [585], MBP (myelin basic protein) [586], ACAN (aggrecan) [587], SHH (sonic hedgehog signaling molecule) [588], SIRT2 [589], RBP4 [590], ISM1 [591], HOXB6 [592], CDH13 [593], NTF3 [594], TRPC6 [595], MMP3 [596], HLA-DRB5 [597], HLA-DRB1 [546], CD74 [598], VWF (von Willebrand factor) [599], MDGA1 [600], ANGPT2 [601], NEDD4L [602], CASP1 [603], CHRNA5 [604], CCND2 [605], BRCA2 [606], TET1 [607], ZBTB20 [608], OAS1 [609], EGFR (epidermal growth factor receptor) [610], ABCA1 [611], PLXNA4 [612], FOXG1 [613], WEE1 [433], MAP1B [614], ANK1 [615], GRM3 [436], COMT (catechol-O-methyltransferase) [616], SLC10A4 [617], GPR39 [618] and LIFR (LIF receptor subunit alpha) [562] could promote Alzheimer’s disease progression. SERPINA1 [619], LRRK2 [620], CHRNA4 [621], TLR2 [622], MOBP (myelin associated oligodendrocyte basic protein) [623], AATK (apoptosis associated tyrosine kinase) [624], MBP (myelin basic protein) [625], SHH (sonic hedgehog signaling molecule) [626], XDH (xanthine dehydrogenase) [627], RBP4 [628], GRIA2 [629], NR3C2 [630], HLA-DRB5 [631], HLA-DRA [631], NEDD4L [632], CASP1 [633], EFNB2 [634], CYP7B1 [635], EGFR (epidermal growth factor receptor) [636], MAP1B [637], GRM3 [638<...…”
Section: Discussionmentioning
confidence: 99%